The phenotypic spectrum of organic acidurias and urea cycle disorders. Part 1: the initial presentation. Issue 6 (15th April 2015) - Kölker, Stefan; Cazorla, Angeles Garcia; Valayannopoulos, Vassili; Lund, Allan M.; Burlina, Alberto B.; Sykut‐Cegielska, Jolanta; Wijburg, Frits A.; Teles, Elisa Leão; Zeman, Jiri; Dionisi‐Vici, Carlo; Barić, Ivo; Karall, Daniela; et al.
Abstract: Background: The clinical presentation of patients with organic acidurias (OAD) and urea cycle disorders (UCD) is variable; symptoms are often non‐specific. Aims/methods: To improve the knowledge about OAD and UCD the E‐IMD consortium established a web‐based patient registry. Results: We registered 795 patients with OAD (n = 452) and UCD (n = 343), with ornithine transcarbamylase (OTC) deficiency (n = 196), glutaric aciduria type 1 (GA1; n = 150) and methylmalonic aciduria (MMA; n = 149) being the most frequent diseases. Overall, 548 patients (69 %) were symptomatic. The majority of them (n = 463) presented with acute metabolic crisis during (n = 220) or after the newborn period (n = 243) frequently demonstrating impaired consciousness, vomiting and/or muscular hypotonia. Neonatal onset of symptoms was most frequent in argininosuccinic synthetase and lyase deficiency and carbamylphosphate 1 synthetase deficiency, unexpectedly low in male OTC deficiency, and least frequently in GA1 and female OTC deficiency. For patients with MMA, propionic aciduria (PA) and OTC deficiency (male and female), hyperammonemia was more severe in metabolic crises during than after the newborn period, whereas metabolic acidosis tended to be more severe in MMA and PA patients with late onset of symptoms. Symptomatic patients without metabolic crises (n = 94) often presented with a movement disorder, mental retardation, epilepsy and psychiatric disorders (the latter in UCD only). Conclusions: The initial presentation varies widely in OAD and UCD patients. This is a challenge for rapid diagnosis and early start of treatment. Patients with a sepsis‐like neonatal crisis and those with late‐onset of symptoms are both at risk of delayed or missed diagnosis.